A gating mutation at the internal mouth of the Kir6.2 pore is associated with DEND syndrome. - Proks, P; Girard, C; Haider, S; Gloyn, A; Hattersley, A; Sansom, MS; Ashcroft, F (2005)
Inwardly rectifying potassium (Kir) channels control cell membrane K+ fluxes and electrical signalling in diverse cell types. Heterozygous mutations in the human Kir6.2 gene (KCNJ11), the pore-forming subunit of the ATP-sensitive (K(ATP)) channel, cause permanent neonatal diabetes mellitus. However, the I296L mutation also results in developmental delay, muscle weakness and epilepsy. We investigated the functional effects of the I296L mutation by expressing wild-type or mutant Kir6.2/SUR1 channels in Xenopus oocytes. The mutation caused a marked increase in resting whole-cell K(ATP) currents by reducing channel inhibition by ATP, in both homomeric and simulated heterozygous states. Kinetic analysis showed that the mutation impaired ATP sensitivity indirectly, by stabilizing the open state of the channel and possibly also by means of an allosteric effect on ATP binding and/or transduction. The results implicate a new region in Kir-channel gating and suggest that disease severity is correlated with the extent of reduction in ATP sensitivity.